Rural exoduses and urbanization in colombia. historical perspective and theoretical approaches (2008)
From the 16th century until today, the migratory phenomenon in Colombia have marked the configuration of the national space and influenced the formation of Colombian urban agglomerations. During the middle of the 20th century, internal migrations from rural areas left historical effects on the country urban net. Rural population, a protagonist since the beginning of century of the agrarian settling in the central Andean region, left the rural zones and headed towards the cities, generating an intense process of urbanization. A theoretical debate about the topic of the causality of the migrations and its influence in the urbanization of the country has been generated in the 60’s and 70’s. The debate is still relevant for the discussion on nowadays urban reconfiguration. From the mid 80’s, Colombia has experienced new rural exoduses caused by an escalation of the armed conflict in rural areas. The massive forced migration today has also a clear influence in the transformation of the contemporary cities. How is forced displacement affecting the current process of urbanization in Colombia? This paper tries to answer this question.